The effects of commercial fibres on frozen bread dough - JELENA FILIPOVIĆ; NADA FILIPOVIĆ; VLADIMIR FILIPOVIĆ (Journal of the Serbian Chemical Society, 2010)
The daily intake of dietary fibres in highly industrialized countries is at a low level and, therefore, adversely affecting human health. The objective of this research was to analyze the influence of different commercial fibres (originating from sugar beet pulp fibrex, and Jerusalem artichoke inulin HPX and GR) in yeast dough at a level of 5 %, on the rheological properties of dough and the quality of bread during frozen storage. Frozen dough characteristics were determined using a Brabender maturograph and test baking was followed according the AACC procedure. The dough was frozen at –18 °C and stored over a period of 60 days. The results concerning the dough (proving time and stability) and bread quality (volume and crumb quality) were statistically analyzed by multivariance Manova and discriminative analysis, which indicated that there was a significant difference between dough without fibres and dough with different fibres (fibrex, inulin HPX and GR). The discrimination coefficient points that the greatest influence of fibres on the final proof and proving stability is after 30 days (6.250) and after 0 days (6.158), respectively, but the greatest influence of fibres on bread volume and bread crumb quality (15.488 and 3.638, respectively) can be expected on non frozen dough, due to above mention their adverse the effect on gluten network.